2022
DOI: 10.7759/cureus.22945
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Rate in Patients With Bladder Cancer According to the Type of Treatment: A Systematic Review

Abstract: Bladder cancer (BC) is classified as a high-risk tumour type for venous thromboembolism (VTE). VTE presents an extra challenge in the management of patients with cancer, given the increase in morbidity and mortality on having both conditions.To summarise the contemporary evidence on the VTE rate in patients with BC according to the stage, type of anti-cancer treatment and highlight VTE rate in the UK and other countries. A systematic review was carried out, and an electronic search for publications between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(41 reference statements)
0
1
0
1
Order By: Relevance
“…To our knowledge, this is the rst report of urothelial cancer as an independent risk factor for the development of ICIinduced TE in carcinoma-speci c multivariate analysis. Previous studies of the association between urothelial cancers and TE suggested that anticancer drug therapy including cisplatin [30][31][32] and surgery of the primary tumor [30,31,33] were associated with TE. In the present study, 40 of the patients had received prior chemotherapy, including cisplatin, and 7 developed TE.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the rst report of urothelial cancer as an independent risk factor for the development of ICIinduced TE in carcinoma-speci c multivariate analysis. Previous studies of the association between urothelial cancers and TE suggested that anticancer drug therapy including cisplatin [30][31][32] and surgery of the primary tumor [30,31,33] were associated with TE. In the present study, 40 of the patients had received prior chemotherapy, including cisplatin, and 7 developed TE.…”
Section: Discussionmentioning
confidence: 99%
“…По данным систематического обзора 38 публикаций, представленного O. Abdullah и соавт., РМП был классифицирован как опухоль высокого риска развития ВТЭ [29]. Общая частота ВТЭ у пациентов с РМП в Великобритании оценивалась в 1,9-4,7 %.…”
Section: актуальная тема Topical Problemunclassified